The Effects of Reduction Mammaplasty on Serum Leptin Levels and Insulin Resistance - Hakan Uzun; Ozan Bitik; Yahya Baltu; Çiğdem Sönmez; Ayşegül Öztürk Kaymak (International Journal of Endocrinology)
Background. The reduction mammaplasty has been a well-executed and known procedure in which considerable amount of fatty tissue is removed from the body. The authors aimed to show the effects of the reduction mammaplasty on serum leptin levels and insulin resistance. Methods. 42 obese female patients who had gigantomastia were operated on. We recorded patients’ demographic and preoperative data, including age, weight, height, and body mass index. Fasting serum leptin, glucose, and insulin levels were noted. Homeostasis model assessment scores were calculated. At the postoperative 8th week, patients were reevaluated in terms of above parameters assessing the presence of any difference. Results. Serum leptin levels were decreased postoperatively and the decrease was statistically significant. We were able to show a decrease in homeostasis model assessment score, which indicated an increase in insulin sensitivity, and this change was statistically significant. A significant correlation between body mass index and leptin change was found postoperatively. Conclusion. Reduction mammaplasty is not solely an aesthetic procedure but it decreases serum leptin levels and increases insulin sensitivity, which may help obese women to reduce their cardiovascular risk.